A low-haze and high-transmittance polyolefin copolymer and its application
By designing the molecular chain structure and α-olefin composition and distribution of polyolefin copolymers, using high-temperature solution polymerization process and jet supplementation technology, the problem of existing polyolefin copolymer materials being difficult to achieve low haze, high light transmittance and high crosslinking efficiency at the same time, and the material's weather resistance and service life are improved.
Patent Information
- Application Number
- CN202310783548.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-06-29
AI Technical Summary
The existing polyolefin copolymer materials are difficult to achieve low haze, high light transmittance and high crosslinking efficiency at the same time, and are insufficient weather resistance, which affects the long-term use efficiency of photovoltaic cells.
By designing the molecular chain structure and α-olefin composition and distribution of polyolefin copolymers, the weight average molecular weight, molecular weight distribution index, haze and light transmittance are regulated, and the crystallization performance and crosslinking point distribution of the copolymer are optimized using high-temperature solution polymerization process and jet supplementation technology.
The low haze, high light transmittance and high crosslinking efficiency of polyolefin copolymers are achieved, and the weather resistance and service life of the material is improved. It is suitable for photovoltaic cells, film materials and seals.
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a polyolefin copolymer product, in particular to a low-haze, high-light-transmittance, easily cross-linked polyolefin copolymer and application thereof. Background Art
[0002] Polyolefin elastomer (POE for short) refers to a random copolymer of ethylene and high-carbon α-olefins. POE commonly referred to mainly refers to ethylene / α-olefin copolymers with an α-olefin mass fraction greater than 20%. This copolymer has the characteristics of low crystallinity and low density. The special molecular composition and microstructure of POE give it the high elasticity and toughness of rubber at room temperature. It can also be plasticized and formed at high temperatures. It has thermal reversibility, excellent mechanical properties, weather resistance and processing rheological properties. In addition, POE has good affinity with polyolefin materials, can effectively enhance low-temperature toughness and is cost-effective, so it is widely used in photovoltaic cells, automotive parts, aerospace, 5G / 6G communications, soles, hot melt adhesives, seals and other fields.
[0003] Compared with traditional polyolefin materials, polyolefin elastomers have higher transparent transmittance, lower haze and better aging resistance, which enables them to play a better role in the fields of film materials with higher requirements for optical properties and weather resistance. In addition, in recent years, countries around the world have gradually required the reduction of carbon emissions, which has also brought new opportunities for the development of clean energy such as photovoltaics. The polyolefin thermoplastic elastomers used in photovoltaic cell encapsulation films have increased year by year. At present, ethylene-vinyl acetate copolymer EVA has become the most commonly used encapsulation film due to its low cost and high transmittance, but EVA is prone to yellowing, bubbling, and its volume resistivity decreases significantly after long-term use, thus affecting the long-term use efficiency of photovoltaic cells. Polyolefin elastomers with a skeleton of carbon and hydrogen atoms have attracted much attention due to their advantages such as good weathering stability, high volume resistivity (two orders of magnitude higher than EVA) and low potential induced attenuation PID. In the future, their use will account for an increasingly higher proportion.
[0004] The optical properties of polyolefin materials determine their photoelectric conversion efficiency, while their weather resistance and strength determine their service life. Currently, methods for improving the transmittance and service life of photovoltaic materials have emerged. For example, patent CN112430435B provides a composite encapsulation film and its preparation method and photovoltaic module, which uses a specific structural setting and the composition of each layer structure to adjust the refractive index of the composite encapsulation film to match the light refraction structure of glass and battery cells, reduce haze, and thus increase light utilization. Patent CN107312468A provides an organosilicon-modified high-transmittance EVA solar cell module encapsulation film, which is mainly modified by organosilicon compounds and multifunctional cross-linking agents. -vinyl acetate copolymer, so that the product has good light transmittance, waterproof performance, bonding strength, electrical properties, bonding performance and excellent anti-PID performance; a reinforced POE photovoltaic encapsulation film described in patent CN109337612A, by blending reinforcing resin, polyethylene fiber and POE, using a compatibilizer to improve the compatibility between the two, and then with thermal conductive powder, high-efficiency degassing agent, cross-linking agent and ultraviolet absorber in a suitable proportion to prepare a POE photovoltaic encapsulation film with high tensile strength, strong aging resistance, not easy to yellow and long service life. However, the above methods are all based on adding modifiers or changing the encapsulation film preparation process, and rarely start from polyolefin elastomer raw materials and preparation methods. Therefore, the present invention aims to disclose a polyolefin copolymer with low haze and high transmittance, and obtains a polyolefin copolymer with low haze, high transmittance, high cross-linking efficiency and good weather resistance by designing the molecular chain structure and regulating the composition and distribution of α-olefins, so as to be used in the field of photovoltaic encapsulation films. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a polyolefin copolymer with low haze and high transmittance and its application. The polyolefin copolymer of the present invention is a copolymer of ethylene and a variety of mixed α-olefins, which can solve the problem that the polyolefin copolymer material in the prior art has low haze, high transmittance, short crosslinking time and good weather resistance.
[0006] Another object of the present invention is to provide the application of the polyolefin copolymer in the fields of film materials, photovoltaic cells, seals, 5G / 6G communications, hot melt adhesives, etc. The polyolefin copolymer has the advantages of easy processing, excellent optical properties, high cross-linking efficiency, and good weather resistance.
[0007] According to one object of the present invention, there is provided a low haze and high transmittance polyolefin copolymer, wherein the polyolefin copolymer is a copolymer of ethylene and α-olefin, has a weight average molecular weight of 10000-400000 g / mol, a molecular weight distribution index of 1-4, a haze of 0.1%-5%, and a transmittance of 88%-99%;
[0008] The polyolefin copolymer is graded into 5 fractions by temperature rising and eluting in the range of 30-105°C, wherein the temperature ranges of the 5 fractions are 30-45°C, 45-60°C, 60-75°C, 75-90°C and 90-105°C respectively, and the comonomer content between adjacent fractions varies in the range of 0.2mol%-1.5mol%, and the comonomer content of the highest temperature fraction in the temperature range of 90-105°C is not less than 5mol%.
[0009] In a low haze and high light transmittance polyolefin copolymer provided by the present invention, the α-olefin is selected from two or more α-olefins having more than 3 carbon atoms and less than 12 carbon atoms, preferably two or more α-olefins selected from 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene. Further, the α-olefin is selected from three or four of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene, and there is not less than one α-olefin having an odd number of carbon atoms. Specifically, the α-olefin is selected from three of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene, and there is at least one α-olefin with an odd number of carbon atoms, and the three α-olefins are olefin A, olefin B, and olefin C (the number of carbon atoms of A is less than the number of carbon atoms of B, and the number of carbon atoms of B is less than the number of carbon atoms of C), and the A / B / C mixed α-olefin is preferably 1-butene / 1-pentene / 1-hexene, 1-butene / 1-pentene / 1-heptene, 1-butene / 1-pentene / 1-octene, 1-butene / 1-pentene / 1-nonene, 1-butene / 1-hexene / One of 1-heptene, 1-butene / 1-hexene / 1-octene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-nonene, 1-pentene / 1-hexene / 1-heptene, 1-pentene / 1-hexene / 1-octene, 1-pentene / 1-hexene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-octene / 1-nonene, 1-hexene / 1-heptene / 1-octene, 1-hexene / 1-heptene / 1-nonene, 1-heptene / 1-octene / 1-nonene.
[0010] According to one aspect of the present invention, the total molar content of α-olefin in the polyolefin copolymer is 2%-40%, and the molar ratio of olefin A, olefin B and olefin C in the α-olefin is (1-4):(1-3):1, preferably (2-3):(1-1.8):1.
[0011] In the low-haze and high-transmittance polyolefin copolymer provided by the present invention, the weight average molecular weight is 10,000-300,000 g / mol, the molecular weight distribution index is 1.3-3.5, the haze is 0.3%-5%, and the transmittance is 90%-98%.
[0012] In a specific embodiment of the present invention, the polyolefin is prepared by a high temperature solution polymerization process, the α-olefin is selected from three of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, and 1-decene, and there is at least one α-olefin with an odd number of carbon atoms, and the three α-olefins are arranged in descending order according to the number of carbon atoms, namely olefin A, olefin B, and olefin C; during the preparation process, olefin A is intermittently added to the reactor in a jet supplement manner, and ethylene, olefin B, and olefin C are added all at once. The molar ratio of olefin A, olefin B, and olefin C in the α-olefin added during the polymerization is (0.5-3):(1-2):1, preferably (1-4):(1-3):1, and more preferably (2-3): (1-1.8): 1; The temperature of the high temperature solution polymerization process is 100-180°C, the pressure is 10-50 bar, the catalyst is selected from one or more of a metallocene catalyst, a late transition metal catalyst, a Ziegler-Natta catalyst, a non-metallocene catalyst, and a FI catalyst, and the co-catalyst is selected from one or more of methylaluminoxane MAO, modified methylaluminoxane MMAO, ethylaluminoxane EAO, butylaluminoxane BAO, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, and tri(2,4,6-trifluorophenyl)borane.
[0013] The present invention also provides the use of the low-fog and high-light-transmittance polyolefin copolymer in the preparation of photovoltaic cells, film materials and sealing components.
[0014] The present invention has the following outstanding benefit effects: (1) by introducing a multi-component mixed α-olefin into the preparation of a polyolefin blend, the molecular chain structure can be optimized by adjusting the insertion ratio of a high-carbon number α-olefin and a low-carbon number α-olefin in the copolymer molecular chain, thereby optimizing the aggregate structure, regulating the crystallization performance, the size and distribution of the lamellae of the polyolefin copolymer, and thus achieving the haze and light transmittance of the polyolefin copolymer. (2) Adding lower carbon number α-olefins into the reactor in the form of jets can achieve macroscopic and microscopic mixing of the co-monomer and the main solution. The externally injected α-olefins drive the main solution to move macroscopically. At the same time, the fluid is broken up by the turbulent vortices of different sizes to form droplets with a certain size distribution, so that the added α-olefins are more evenly distributed in the main solution, thereby forming a short-term alternating balance between olefin-rich streams and uniform olefin streams, forming a polyolefin blend with high and low carbon number α-olefin content and stable and uniform distribution; and more low carbon number α-olefins inserted into the molecular chain will change the crystal morphology of the polymer, forming more uniform and fine crystalline structures, and improving the light transmittance of the polymer; (3) More low carbon number α-olefins inserted into the molecular chain are conducive to the formation of more branched structures on the main chain, forming more cross-linking points, and improving the cross-linking efficiency of the polyolefin copolymer. DETAILED DESCRIPTION
[0015] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0016] The following methods were used to test the structure or properties of the polyolefins produced in the examples described:
[0017] High temperature gel permeation chromatography (GPC) is used to test the molecular weight and distribution index of polyolefins.
[0018] Photoelectric haze meter is used to test the haze and transmittance of polyolefins.
[0019] Differential Scanning Calorimetry (DSC) is used to measure the melting point and glass transition temperature of polyolefins.
[0020] The temperature rising elution fractionation equipment is used to separate different temperature fractions in polyolefin elastomers.
[0021] Nuclear Magnetic Resonance Spectrometer ( 1 H-NMR, 13 C-NMR) is used to test the α-olefin insertion rate and branching structure characterization of polyolefin materials.
[0022] Example 1
[0023] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 3 μmol of metallocene catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 140°C, and 1L of hexane, 170 mL of mixed α-olefins were added in sequence, including 90 mL of 1-hexene and 80 mL of 1-heptene, and then 2 mmol of co-catalyst methylaluminoxane and 3 μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 30 bar, and the polymerization was carried out for 25 minutes. During the polymerization reaction, 130 mL of 1-pentene was supplemented by jet interruption. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0024] Example 2
[0025] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 1.2 μmol of metallocene catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 110°C, and 1L of hexane, 190 mL of mixed α-olefins were added in sequence, including 120 mL of 1-hexene and 70 mL of 1-octene, and then 1.6 mmol of co-catalyst methylaluminoxane and 1.2 μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 20 bar, and the polymerization was carried out for 20 minutes. During the polymerization reaction, 260 mL of 1-pentene was added by interrupting the jet flow. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0026] Example 3
[0027] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2.2 μmol of metallocene catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 160°C, and 1L of hexane, 310 mL of mixed α-olefins were added in sequence, including 200 mL of 1-hexene and 110 mL of 1-nonene, and then 2 mmol of co-catalyst methylaluminoxane and 2.2 μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 40 bar, and the polymerization was carried out for 30 minutes. During the polymerization reaction, 290 mL of 1-pentene was supplemented by jet interruption. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0028] Example 4
[0029] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of non-metallocene catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 180°C, and 1L of hexane, 600mL of mixed α-olefins, including 250mL of 1-heptene and 350mL of 1-octene, were added in sequence, and then 1.2mmol of co-catalyst methylaluminoxane and 2μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 50 bar, and the polymerization was carried out for 40 minutes. During the polymerization reaction, 600mL of 1-hexene was added by interrupting the jet flow. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0030] Example 5
[0031] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of the late transition metal catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 130°C, and 1L of hexane, 500mL of mixed α-olefins were added in sequence, including 300mL of 1-hexene and 200mL of 1-octene, and then 1.3mmol of co-catalyst methylaluminoxane and 2μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 30 bar, and the polymerization was carried out for 40 minutes. During the polymerization reaction, 300mL of 1-pentene was added by interrupting the jet flow. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0032] Example 6
[0033] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of non-metallocene catalyst was dissolved in 1 ml of hexane for standby use. The temperature of the polymerization reactor was adjusted to 120°C, and 1L of hexane, 180 mL of mixed α-olefins were added in sequence, including 100 mL of 1-heptene and 80 mL of 1-nonene, and then 2 mmol of co-catalyst methylaluminoxane and 2 μmol of metallocene catalyst were added in sequence, ethylene was introduced, the ethylene pressure was 28 bar, and the polymerization was carried out for 30 minutes. During the polymerization reaction, 120 mL of 1-hexene was added by interrupting the jet flow. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0034] Comparative Example 1
[0035] The polymerization reaction apparatus was purged with high-purity nitrogen to remove moisture and oxygen inside the reaction apparatus. 2 μmol of metallocene catalyst was dissolved in 1 ml of toluene for standby use. The temperature of the polymerization reactor was adjusted to 130°C, and 1L of hexane and 300mL of 1-hexene were added in sequence, followed by 2mmol of cocatalyst methylaluminoxane and 2 μmol of metallocene catalyst, and ethylene was introduced at an ethylene pressure of 30 bar for 30 minutes. The relevant characterization and performance test results of the obtained products are shown in Tables 1 and 2.
[0036] Comparative Example 2
[0037] The commercially available polyolefin elastomer PV8660 of Dow was tested according to the above characterization method. The relevant characterization and performance test results of the obtained product are shown in Table 1 and Table 2.
[0038] Table 1 Related performance test results of polyolefin products
[0039]
[0040]
[0041] Table 2 Comonomer content of each fraction of elution fraction of polyolefin products
[0042]
[0043] Note: Fractions Ⅰ, Ⅱ, Ⅲ, Ⅳ and Ⅴ are separated step by step according to the elution temperature from low to high.
[0044] As shown in Table 1 and Table 2 above, the polyolefin copolymers prepared by Example 2 and Comparative Example 1 have similar molecular weights and distributions, but Example 2 is formed by copolymerization of mixed α-olefins (1-pentene / 1-hexene / 1-heptene) and ethylene, and its haze and transmittance are significantly better than those of the sample in Comparative Example 1. This is mainly because the comonomer content of the polyolefin copolymer of Example 2 in different fractions is relatively balanced, and the comonomer content decreases at a lower rate with the increase of melting point (increase of fractions), so that its lamellae are smaller in size and more in number, thereby weakening the scattering effect of light, improving transmittance and reducing haze. The comonomer content of the sample in Comparative Example 1 in different fractions is quite different, and the comonomer content of the high melting point part is reduced to a greater extent than that of the low melting point part, resulting in a larger lamellae size in the high melting point part, thereby enhancing the scattering and reflection effect of light, reducing transmittance and increasing haze. The sample of Example 6 and the sample of Comparative Example 2 have similar molecular weights and distributions and comonomer alpha olefin insertion rates, but the sample of Example 6 is copolymerized with mixed alpha olefins (1-hexene / 1-heptene / 1-nonene) and ethylene, and its haze and transmittance are better than the sample of Comparative Example 2, which is also due to the fact that the comonomer content of the sample of Example 6 decreases less with increasing melting point, and the lamella size is smaller and more fragmented, so that its transmittance is improved and the haze is reduced. It can be seen that the polyolefin copolymer disclosed in the present invention has the characteristics of low haze, high transmittance and high cross-linking efficiency of molecular chain segments, which is significantly better than commercial polyethylene elastomer materials available on the market, and can be widely used in photovoltaic cells, membrane materials, seals, 5G / 6G communications and other fields.
[0045] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A low haze and high light transmittance polyolefin copolymer, characterized in that: The polyolefin copolymer is a copolymer of ethylene and α-olefin, with a weight average molecular weight of 10,000-400,000 g / mol, a molecular weight distribution index of 1-4, a haze of 0.1%-5%, and a light transmittance of 88%-99%; The polyolefin copolymer is graded into 5 fractions by temperature rising and eluting in the range of 30-105°C, wherein the temperature ranges of the 5 fractions are 30-45°C, 45-60°C, 60-75°C, 75-90°C and 90-105°C respectively, and the comonomer content between adjacent fractions varies in the range of 0.2mol%-1.5mol%, and the comonomer content of the highest temperature fraction in the temperature range of 90-105°C is not less than 5mol%.
2. The low haze and high light transmittance polyolefin copolymer according to claim 1, characterized in that: The α-olefins are selected from two or more α-olefins having more than 3 carbon atoms and less than 12 carbon atoms.
3. The low haze and high light transmittance polyolefin copolymer according to claim 2, characterized in that: The α-olefin is selected from two or more of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene and 1-decene.
4. The low haze and high light transmittance polyolefin copolymer according to claim 3, characterized in that: The α-olefins are selected from three or four of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene and 1-decene, and the α-olefins having odd carbon atoms are not less than one.
5. The low haze and high light transmittance polyolefin copolymer according to claim 4, characterized in that: The α-olefins are selected from three of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene and 1-decene, and there is at least one α-olefin with an odd number of carbon atoms. The three α-olefins are olefin A, olefin B and olefin C, respectively. The number of carbon atoms of olefin A is less than that of olefin B, and the number of carbon atoms of olefin B is less than that of olefin C.
6. The low haze and high light transmittance polyolefin copolymer according to claim 4, characterized in that: The combination of three α-olefins is 1-butene / 1-pentene / 1-hexene, 1-butene / 1-pentene / 1-heptene, 1-butene / 1-pentene / 1-octene, 1-butene / 1-pentene / 1-nonene, 1-butene / 1-hexene / 1-heptene, 1-butene / 1-hexene / 1-nonene, 1-butene / 1-heptene / 1-octene, 1-butene / 1-heptene / 1-nonene, 1-pentene / 1-hexene / 1-heptene, 1-pentene / 1-hexene / 1-octene, 1-pentene / 1-hexene / 1-nonene, 1-pentene / 1-heptene / 1-octene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-heptene / 1-nonene, 1-pentene / 1-octene / 1-nonene, 1-hexene / 1-heptene / 1-octene, 1-hexene / 1-heptene / 1-nonene, 1-heptene / 1-octene / 1-nonene.
7. The low haze and high light transmittance polyolefin copolymer according to claim 5, characterized in that: The total molar content of α-olefin in the polyolefin copolymer is 2%-40%, and the molar content ratio of olefin A, olefin B and olefin C is (1-4): (1-3):
1.
8. The low haze and high light transmittance polyolefin copolymer according to claim 5, characterized in that: The total molar content of alpha-olefin in the polyolefin copolymer is 2%-40%, and the molar content ratio of olefin A, olefin B and olefin C is (2-3): (1-1.8):
1.
9. The low haze and high light transmittance polyolefin copolymer according to claim 1, characterized in that: The weight average molecular weight of the polyolefin copolymer is 10000-300000 g / mol, the molecular weight distribution index is 1.3-3.5, the haze is 0.3%-5%, and the light transmittance is 90%-98%.
10. A low haze and high light transmittance polyolefin copolymer according to any one of claims 1 to 9, characterized in that: The α-olefins are selected from three of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene and 1-decene, and there is at least one α-olefin with an odd number of carbon atoms, and the three α-olefins are arranged in descending order according to the number of carbon atoms, namely olefin A, olefin B and olefin C; the polyolefin copolymer is prepared by a high-temperature solution polymerization process, during which olefin A is intermittently added to the reactor in a jet supplement manner, and ethylene, olefin B and olefin C are added all at once, and the molar ratio of olefin A, olefin B and olefin C in the α-olefin added during the polymerization is (0.5-3):(1-2):1; high-temperature solution polymerization process The temperature is 100-180° C., the pressure is 10-50 bar, the catalyst is selected from one or more of a metallocene catalyst, a late transition metal catalyst, a Ziegler-Natta catalyst, a non-metallocene catalyst, and a FI catalyst, and the co-catalyst is selected from one or more of methylaluminoxane MAO, modified methylaluminoxane MMAO, ethylaluminoxane EAO, butylaluminoxane BAO, trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, triphenylborane, tri(4-fluorophenyl)borane, tri(pentafluorophenyl)borane, tri(3,5-difluorophenyl)borane, and tri(2,4,6-trifluorophenyl)borane.
11. The low haze and high light transmittance polyolefin copolymer according to claim 10, characterized in that: The molar ratio of olefin A, olefin B and olefin C added in the α-olefin during polymerization is (1-4):(1-3):
1.
12. The low haze and high light transmittance polyolefin copolymer according to claim 10, characterized in that: The molar ratio of olefin A, olefin B and olefin C added in the α-olefin during polymerization is (2-3):(1-1.8):
1.
13. Use of the low-haze and high-transmittance polyolefin copolymer according to any one of claims 1 to 9 in the preparation of photovoltaic cells, film materials, and sealants.
Citation Information
Patent Citations
Organosilicon-modified high-transmittance EVA solar cell assembly encapsulating adhesive film
CN107312468A
Enhanced POE (poly(ethylene-co-1-octene)) photovoltaic encapsulation adhesive film
CN109337612A
Ethylene polymer, thermoplastic resin composition comprising the polymer, and molded article
CN101268108A
Polyethylene
CN105732870A